Molecular genetic characterization of different isolates of Echinococcus granulosus in east and southeast regions of Turkey - Utuk, Armagan Erdem; Simsek, Sami; Koroglu, Ergun; McManus, Donald P. (Elsevier, 2008)
We used PCR-RFLP analysis of ribosomal ITS1 fragment using four different restriction enzymes and DNA sequencing of mitochondrial CO1 gene to investigate the genetic characteristics of isolates of Echinococcus granulosus obtained from different hosts (179 sheep, 19 cattle, 7 goat, 1 camel, 1 dog and 1 human) and regions (Elazig, Malatya, Erzurum, Van, Diyarbakir and Sanliurfa) of Turkey. The report represents the most comprehensive genotypic investigation of E. granulosus isolates undertaken in Turkey, with Turkish samples of cattle, goat, camel and dog origin being characterized for the first time. We show that the predominant genotype involved in E. granulosus; transmission in Turkey is the common sheep strain (G1 genotype) infecting humans, cattle, sheep, goats, camels as well as the dog definitive host. Nevertheless, we urge that coordinators of local control programs in Turkey should take into consideration the potential occurrence and risk of additional strains of E. granulosus infecting humans and animal hosts, and plan accordingly. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Echinococcus granulosus; PCR-RFLP; DNA sequence; genotyping; Turkey